2019
DOI: 10.5005/jp-journals-10024-2672
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Ethanol-extracted Bixa orellana (L) (Achiote) on Candida albicans, at Six Different Concentrations

Abstract: Aim:The aim of the study was to determine the antifungal activity of six different concentrations of the ethanol extract of Bixa orellana (L) (Achiote) on the strains of Candida albicans (ATCC 90028). Materials and methods: The ethanol extract of Bixa orellana (L) (BEE) was prepared in six different concentrations (5%, 10%, 20%, 40%, 60%, and 100%), which were confronted with the positive control group (Nystatin 100,000 UI/mL). The total sample consisted of n = 174 wells inoculated with each concentration eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
13
0
4
Order By: Relevance
“…Multiple studies have demonstrated its important medicinal properties. However, its antibacterial effectiveness against S. mutans , which has shown a relevant role in the pathogenesis of different oral diseases, has not yet been demonstrated [ 3 5 ]. Tooth decay is one of the most prevalent diseases in Peru, and it is associated with different etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated its important medicinal properties. However, its antibacterial effectiveness against S. mutans , which has shown a relevant role in the pathogenesis of different oral diseases, has not yet been demonstrated [ 3 5 ]. Tooth decay is one of the most prevalent diseases in Peru, and it is associated with different etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the cytotoxic reactions of the sealants and their inability to completely remove bacteria from the dentinal tubules, there is now a trend to using natural plant extracts. [ 8 9 10 11 ] A sealant based on zinc oxide and eugenol with herbal extracts produced larger inhibitory zones followed, in descending order, by a resin-based sealer, and Ca(OH) 2 along with the three herbal extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the use of natural products as a new antimicrobial alternative,[ 8 9 10 11 ] and have described the importance of the application of substances such as intraconduction medication in pieces with asymptomatic apical periodontitis to eliminate existing bacteria, and also to achieve successful duct treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Direct observation was made, and the measurement of the inhibitory halo (Kirby–Bauer method)[ 6 8 9 10 ] of four concentrations at 25%, 50%, 75%, and 100% of the EOC and nystatin on strains of Candida albicans ATCC 10231 was taken; the data obtained was recorded in a data collection sheet where the inhibition halos measurements in millimeters, formed in each of the discs embedded with the EOC. In the period of 24 and 48h of having made the sowing, the readings and filling of the collection sheet were made, taking into account the identification of the sample, identification of the concentration used, and the measurement in millimeters of the halo of inhibition formed [ Figure 2 ].…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The great variety of natural resources such as Cinnamomum zeylanicum (Canela) has empirically and methodologically shown its effectiveness on a number of microorganisms. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%